Antineutrophil cytoplasmic antibody-negative granulomatosis with polyangiitis localized to the lungs - Yuichi Ohteru; Kazuki Hamada; Keiji Oishi; Junki Suizu; Misa Harada; Keita Murakawa; Ayumi Chikumoto; Kazuki Matsuda; Sho Uehara; Shuichiro Ohata; Yoriyuki Murata; Yoshikazu Yamaji; et al. (Respiratory Medicine Case Reports, 2022)
Patients with granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis, sometimes exhibit no clinical features. Here, we describe a case of antineutrophil cytoplasmic antibody (ANCA)-negative GPA presenting with only lung granuloma. A 55-year-old woman with a right upper lung mass underwent lobectomy for suspected lung cancer; however, only granuloma was detected, and the etiology was not identified. Serum ANCA results were negative. Four years postoperatively, another pulmonary nodule appeared in the left lung's apex. The kidneys and sinuses were not impaired, but re-examination of the resected specimen revealed necrotizing vasculitis and granulomas around the vessels. Thus, the patient was diagnosed with GPA localized to the lungs. Although this was a non-life-threatening disease, the patient was administered oral prednisolone (PSL) and intravenous cyclophosphamide (IVCY) to prevent fatal complications of GPA as she was non-elderly and had no comorbidities, leading to a decrease in the mass size. Detailed re-examination by expert pulmonary pathologists could aid in GPA diagnosis when clinical features are absent, as in our case. In patients with granulomas of unknown etiology, a careful multidisciplinary approach is pivotal in the diagnosis. If patients tolerate adverse effects, a PSL and IVCY combination may prevent fatal outcomes, even in patients with non-life-threatening disease.